Hubungan Antara Karakteristik Orang Tua Dengan Implementasi Fungsi Perawatan Kesehatan Keluarga Dengan Balita - Irwina Angelia Silvanasari; M. Elyas Arif Budiman (LPPM Universitas dr. Soebandi, 2022)
Introduction: The prevalence of various health problems in the aggregate of toddlers is still quite high in Indonesia. The role of the family is needed, especially in optimizing the implementation of the health care function in order to be able to improve the health quality of toddlers. Objective: Analyzing the correlation between the parental character and the health care function implementation of families with toddler is study's purpose. Methods: Cross sectional quantitative design was carried out in this study. The population in this study was the entire family of toddlers. The research sample was 100 families with a sampling technique using purposive sampling. Results: The independent variables were the characteristics of parents including parent education (mom and dad), family revenue, and profession of mother. The dependent variable included the health care function implementation of families with toddler. Conclusion: Mother’s education, family revenue, and mother’s profession didn’t have a significant relationship with the health care function implementation of families with toddler. There was a correlation between father's education and the health care function implementation of families with toddler. A father's high education will help fathers in making wise decisions about children health in the family. Health education related to optimizing health care functions should be provided by nurses to parents.